Multicultural Society Development Dimensions of Diversity and Cultural Change - Fatimah, Siti (International Journal of Islamicate Social Studies, 2023)
This article aims to analyze more deeply about multiculturalism in Indonesia. This country is a strong nation and has a variety of cultures, ethnicities, tribes, flavors, and even religions. All these differences have also become a necessity for the Indonesian people. This research uses the literature method. The results found that a multicultural society is a society that has various elements such as religion, education, language, race, tribe, and even economy, but lives in one group and one government. Multicultural societies are formed from an understanding of these understandings, not just acknowledging differences but also understanding diversity. Recognition of plurality minimizes conflict over primordial or sectarian issues. When viewed from a cultural perspective, multiculturalism views society as a cultural reality with a pattern like a mosaic.